2019
DOI: 10.1108/gm-11-2017-0145
|View full text |Cite
|
Sign up to set email alerts
|

Economic empowerment of Iranian women through the internet

Abstract: Purpose This paper aims to explore the extent to which the internet has created new opportunities for Iranian women in Tehran. It analyses both challenges and opportunities offered to Iranian women by the internet as a means of economic empowerment. Design/methodology/approach This paper adopts a qualitative approach and based on 13 semi-structured interviews with female internet users between the ages of 20 and 55 years. The qualitative data was collected through open-ended questions in face-to-face intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Skilled shoppers are likely to exhibit strong purchase intentions (McLean et al, 2020). Golzard (2019) has also suggested that urban working women develop superior capabilities for Internet usage and have more confidence in performing online transactions. Since Internet self-efficacy can act as stimuli for buying intentions in e-commerce and working women demonstrate higher online shopping self-efficacy, we posit: H1.…”
Section: Internet Self-efficacy and Purchase Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skilled shoppers are likely to exhibit strong purchase intentions (McLean et al, 2020). Golzard (2019) has also suggested that urban working women develop superior capabilities for Internet usage and have more confidence in performing online transactions. Since Internet self-efficacy can act as stimuli for buying intentions in e-commerce and working women demonstrate higher online shopping self-efficacy, we posit: H1.…”
Section: Internet Self-efficacy and Purchase Intentionmentioning
confidence: 99%
“…Working women with an adequate level of Internet self-efficacy possess related knowledge and skills. Hence, they require less guidance and support in performing online transactions and develop a positive attitude towards performing tasks digitally (Golzard, 2019). Researchers have found a positive perception of computer self-efficacy affecting perceived benefits from its usage (Thongsri et al, 2020).…”
Section: Internet Self-efficacy and Perceived Benefitsmentioning
confidence: 99%
“…On the other hand, although Iranian women entrepreneurs in general suffer from issues such as mobility restrictions, which may limit their access to training and career opportunities (Metcalfe, 2008), lack of organizational support (Jamali and Nejati, 2009) and many unique cultural challenges (Javadian and Singh, 2012), the number of Iranian women who are starting businesses is increasing in Iran (Sarfaraz, 2016). In other words, while numerous inequalities impact Iranian women's economic activities profusely, more new businesses are established in Iran by an increasing number of highly educated women (Golzard, 2019).…”
Section: Iranian Women Entrepreneursmentioning
confidence: 99%
“…ICT can also be applied to empower participants in their own ICT usefor example, empowering women and girls in the use of digital technologies to improve their outlook on the job market. As this focuses largely on the use of internet services which do not require specialized IT skills (Golzard 2019), this would be neither lightweight or heavyweight IT. But the complementary examples of rural access centers in this context would have to be classified as heavyweight IT, as they require IT specialists to run (Buskens and Webb 2009).…”
Section: Programme Deliverymentioning
confidence: 99%